Determining the Effect of Soapnut (Sapindus mukorossi) on In Vitro Methanogenesis and Dry Matter Degradation in Cross-Bred HF Cattle - S.V. Rathod; P. R. Pandya; G. P. Mathukiya; K. K. Sorathiya; R. K. Dangi; B. R. Devalia (Indian Journal of Animal Nutrition, 2024)
Soapnut fruits have high saponin content about 10% of fruits. An in-vitro studies were undertaken for explore the effects of different levels of Soapnut fruits on methanogenesis, total gas production, and dry matter degradation by using rumen liquor of CB HF cattle. Their nine treatments of three replicates each follows: Soapnut powder added at 0, 1, 2, up to 8% on DM basis with finely grinded TMR in 100ml in vitro syringe. Among those treatments, reduction of methane gas was non significance (P>0.05), where reduction percent was recorded in S1, S2, S3, S5, S7, and S8 Soapnut supplementation i.e., 22.16, 15.78, 5.54, 14.40, 5.54 and 9.42% respectively, per 100 mg DDM compared to control S0 group. While methane gas production at S4 and S6 was at par as control S0 group. The total gas production during methane production was not differed (P>0.05) but, reduced up to 19.68, 13.64, 25.77, 15.18, and 22.73% respectively, in S1, S3, S5, S7, and S8 treatment groups compared to control. The DMD in S1 and S2 was increased up to 7.04 and 9.12% respectively, but other Soapnut treatment reduces DM degradation. Their highest DM degradation reduction observed in S4, S5, and S8 treatments i.e., 8.94, 6.82, and 9.12% respectively, compared to the control S0 treatment. The IVDMD of Soapnut supplementation was reduced with increasing level of Soapnut supplementation.